Excessive gestational weight gain and obesity contribute to altered expression of maternal insulin-like growth factor binding protein-3 - Ferraro ZM; Qiu Q; Gruslin A; Adamo KB (Dove Medical Press, 2013)
Zachary M Ferraro,1 Qing Qiu,2 Andrée Gruslin,3,4 Kristi B Adamo1,3,5 1Healthy Active Living and Obesity Research Group, Children's Hospital of Eastern Ontario Research Institute, Ottawa, ON, Canada; 2The Ottawa Hospital Research Institute, Ottawa, ON, Canada; 3Faculty of Health Sciences, School of Human Kinetics, University of Ottawa, Ottawa, ON, Canada; 4Departments of Obstetrics and Gynecology, Division of Maternal-Fetal Medicine and Cellular and Molecular Medicine, University of Ottawa, Ottawa, ON, Canada; 5Department of Pediatrics, University of Ottawa, Ottawa, ON, Canada Background: Excessive gestational weight gain (GWG) increases risk of large for gestational age neonates and subsequent tracking of excess weight throughout the life course for both mother and child. Although the physiological mechanisms underlying these associations are incomplete, the insulin-like growth factor (IGF) axis has garnered attention for its role in fetal growth and development. Our purpose was to characterize the IGF axis protein expression patterns in mother–infant dyads in respect of excessive GWG. Methods: We obtained fasting serum samples and corresponding cord blood from eight controls (ADHERE group: ie, those who gained in accordance with 2009 Institute of Medicine GWG recommendations) and 13 exceeders (EXCEED group: ie, those who exceeded Institute of Medicine GWG recommendations). At study completion, we examined protein expression of IGF-I, IGF-II, IGF binding protein (IGFBP)-1, IGFBP-3, IGFBP-4, and hormone concentrations in both maternal and cord blood. Results: Between-group comparisons were made and revealed elevated maternal leptin (P ≤ 0.05) concentrations in gravidas who exceeded recommendations. There was a significantly higher number of obese women in the EXCEED group (P < 0.05). After adjustment, maternal leptin levels were positively correlated with maternal homeostasis model of assessment for insulin resistance score and excessive GWG (P ≤ 0.01). However, serum IGFBP-3 expression in the EXCEED mothers was greater than that in the ADHERE group (P ≤ 0.05). Conclusion: These findings provide preliminary evidence suggesting that small deviations in IGFBP-regulated IGF bioavailability arising from excessive GWG/positive energy balance may affect adipocyte differentiation through subclinical insulin resistance. Keywords: gestational weight gain, insulin-like growth factors, insulin-like growth factor binding protein-3, pregnancy, insulin sensitivity